Basic principles in achieving a good relationship with the Media in Administration - Rus, Mihaela; Tasențe, Tănase; Sandu, Mihaela Luminița; Burcă, Andreea Ioana (Technium Social Sciences Journal, 2021)
Especially in diplomatic relations, a good relation between the embassies and the local mass-media can make a major contribution to strengthening relations between the two countries, both socially and economically. An administration with a good image in the mentality of public opinion must take the citizens into account, it must build basic principles on which they can fulfill the promises made to them, to respect the decisions adopted, so it leads to the good achievement of everything. That is why specialists recommend some basic principles when we want to achieve a very good relationship with the media, and namely: knowing the public, choosing a patient storyteller, focusing the results on activities, moving beyond the room echo-concentration of attention outside the walls of the business, the company must provide confidence, must be in accordance with the promise and delivery of information and appeal to action. This paper is structured in 3 chapters. The first two chapters address the topic from a theoretical point of view, and the third chapter is dedicated to a case study on the communication strategy with the media of the U.S. Embassy in Bucharest.